Phylogeographic patterns of Deschampsia cespitosa (Poaceae) in Europe inferred from genomic data - Xue, Zhiqing; Chiapella, Jorge Oscar; Paun, Ovidiu; Volkova, Polina; Peintinger, Markus; Wasowicz, Pawel; Tikhomirov, Nikita; Grigoryan, Maksim; Barfuss, Michael H. J.; Greimler, Josef (Botanical Journal of the Linnean Society)
The highly variable tufted hairgrass Deschampsia cespitosa is a tussock-forming plant especially of cool and humid environments. Although common and widespread, its phylogeographic structure and the significance of polyploidy for its evolution are poorly understood. Here we used a phylogenomic approach to study the genetic structure of this species in Europe and how the polyploid cytotypes/subspecies are related to the diploids. Using genomic data (RADseq and wholeplastid sequencing) we found a highly divergent Iberian group, including the Spanish Deschampsia cespitosa subsp. cespitosa (diploid and tetraploid) and the Macaronesian island endemic diploid Deschampsia argentea. Moreover, we found substantial divergence of pseudoviviparous tetraploids (Deschampsia cespitosa subspp. neoalpina and rhenana) from seminiferous tetraploids (except Deschampsia cespitosa subsp. littoralis) and all diploids of the remainingEuropean samples. The divergent pseudoviviparous tetraploids (D. cespitosa subspp. neoalpina and rhenana) and the seminiferous tetraploid D. cespitosa subsp. littoralis probably represent periglacial and relict lineages of unknown origin regarding auto- and/or allo-polyploidy, whereas other seminiferous tetraploid variants of D. cespitosa are always nested in the diploid D. cespitosa, suggesting multiple autopolyploid origins. An analysis after excluding the IberianGroup and the highly divergent tetraploids revealed five genetic groups with overlapping geographical patterns. However, the recovered geographical structure, the overall low genetic divergence and the diffuse genetic structure point to recolonization from various refugial areas and secondary contact. Effective wind dispersal of pollen and seeds in an open early post-glacial tundra landscape and, finally, increasing human impact on dispersal of this grass since theNeolithic, may have enhanced admixture and resulted in the complex patterns detected today. Fil: Xue, Zhiqing. Universidad de Viena. Instituto de Botanica; Austria Fil: Chiapella, ...